Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3402/fnr.v60.31382
|View full text |Cite
|
Sign up to set email alerts
|

In vivoprotein quality of selected cereal-based staple foods enriched with soybean proteins

Abstract: BackgroundOne way to diminish protein malnutrition in children is by enriching cereal-based flours for the manufacturing of maize tortillas, wheat flour tortillas, and yeast-leavened breads, which are widely consumed among low socio-economic groups.ObjectiveThe aim was to determine and compare the essential amino acid (EAA) scores, protein digestibility corrected amino acid scores (PDCAAS), and in vivo protein quality (protein digestibility, protein efficiency ratio (PER), biological values (BV), and net prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
(39 reference statements)
2
14
1
Order By: Relevance
“…Consequently, the amino acid scores (see Table ) of enriched tortillas improved in about 11 and 21 units, respectively. This effect was previously observed by Acevedo‐Pacheco and Serna‐Saldívar () in their research related to the production of fortified corn tortillas with defatted soybean flour. In vitro protein digestibility was evaluated and results indicated that this parameter was not affected by the partial substitution of NCF by 5 or 10SB (about 90% in all tortillas).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Consequently, the amino acid scores (see Table ) of enriched tortillas improved in about 11 and 21 units, respectively. This effect was previously observed by Acevedo‐Pacheco and Serna‐Saldívar () in their research related to the production of fortified corn tortillas with defatted soybean flour. In vitro protein digestibility was evaluated and results indicated that this parameter was not affected by the partial substitution of NCF by 5 or 10SB (about 90% in all tortillas).…”
Section: Resultssupporting
confidence: 76%
“…More importantly, the PDCAAS of the SB tortillas improved mainly due to the higher levels of lysine and tryptophan (Table ). The most limiting amino acids for these tortillas were lysine followed by tryptophan (Acevedo‐Pacheco & Serna‐Saldívar, ). Results show that lysine levels were 14% and 26% higher in tortillas containing 5SB and 10SB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cereals, as edible grains belonging to Gramineae family, have been cultivated before civilization period due to high nutritional value and palatability Beloshapka, Buff, Fahey, & Swanson, 2016. Although only, few of them (especially wheat and rice) have been extensively used as staple foods for human consumption, majority such as barley and sorghum have been utilized as livestock feed (Acevedo-Pacheco & Serna-Saldívar, 2016). However, cereal grains can be a significant source of risk for both human and animal due to the presence of mycotoxins especially aflatoxins (AF) as a potent natural toxin (Duarte, Pena, & Lino, 2010;Khaneghah, Martins, Von Hertwig, Bertoldo, & Sant'ana, 2018a;Wild & Gong, 2009), cereals-based products can be classified as one of the leading sources of food and feed for human and animal.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained values for R2 and R3 were similar to those found by Pinto Kramer 22 in other bakery foods nutritionally enhanced: for example, cookies elaborated with 70:30 soy and oats (SCh=96%); sweet biscuits with 80:20 soybean/ rice (SCh=94%); and biscuits made with 60:40 soybean/ amaranth (SCh=92%), with lysine as limiting amino acid in all cases. Acevedo-Pacheco and Serna-Saldívar 23 enriched corn and wheat tortillas with 6% of defatted soybean flour and achieved an increase in protein intake of 25 and 23% respectively, with chemical score improved from 49 to 64%.…”
Section: Discussionmentioning
confidence: 98%